The Discovery and Development of Oxalamide and Pyrrole Small Molecule Inhibitors of gp120 and HIV Entry - A Review - Motati, Damoder R.; Uredi, Dilipkumar; Watkins, E. Blake (Current Topics in Medicinal Chemistry, 2019)
Human immunodeficiency virus type-1 (HIV-1) is the causative agent responsible for the acquired immunodeficiency syndrome (AIDS) pandemic. More than 60 million infections and 25 million deaths have occurred since AIDS was first identified in the early 1980s. Advances in available therapeutics, in particular combination antiretroviral therapy, have significantly improved the treatment of HIV infection and have facilitated the shift from high mortality and morbidity to that of a manageable chronic disease. Unfortunately, none of the currently available drugs are curative of HIV. To deal with the rapid emergence of drug resistance, off-target effects, and the overall difficulty of eradicating the virus, an urgent need exists to develop new drugs, especially against targets critically important for the HIV-1 life cycle. Viral entry, which involves the interaction of the surface envelope glycoprotein, gp120, with the cellular receptor, CD4, is the first step of HIV-1 infection. Gp120 has been validated as an attractive target for anti-HIV-1 drug design or novel HIV detection tools. Several small molecule gp120 antagonists are currently under investigation as potential entry inhibitors. Pyrrole, piperazine, triazole, pyrazolinone, oxalamide, and piperidine derivatives, among others, have been investigated as gp120 antagonist candidates. Herein, we discuss the current state of research with respect to the design, synthesis and biological evaluation of oxalamide derivatives and five-membered heterocycles, namely, the pyrrole-containing small molecule as inhibitors of gp120 and HIV entry.
Keywords: Pyrroles